THE PRINCIPLE OF AMBIVALENCE IN JUDGEMENTS IN FOREIGN LANGUAGE TEACHING: THEORETICAL FOUNDATIONS AND PRACTICAL IMPLEMENTATION - Holovko, Iryna (SWorld-Ger Conference proceedings, 2025)
This paper explores the theoretical and methodological foundations of the principle of ambivalence in judgments as a pedagogical strategy in foreign language education. In the theoretical section, ambivalence is examined through philosophical and psychol